2018
DOI: 10.1159/000492651
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Deficiency Protects Heart from High Fat Diet-Induced Oxidative Stress Via Activating Sirt3/FOXO3 Pathway

Abstract: Background/Aims: Previous studies showed that CD38 deficiency protected heart from ischemia/reperfusion injury and high fat diet (HFD)-induced obesity in mice. However, the role of CD38 in HFD-induced heart injury remains unclear. In the present study, we have investigated the effects and mechanisms of CD38 deficiency on HFD-induced heart injury. Methods: The metabolites in heart from wild type (WT) and CD38 knockout (CD38-/-) mice were examined using metabolomics analysis. Cell viability, lactate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 61 publications
(67 reference statements)
0
29
0
Order By: Relevance
“…NAD + concentrations were decreased in animals during aging and senescence (Verdin, 2015). Our previous study also demonstrated that CD38 played vital roles in adipogenesis and high fat induced oxidative stress (Wang et al, 2018a, b). But the role of CD38 in heart aging was unknown.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…NAD + concentrations were decreased in animals during aging and senescence (Verdin, 2015). Our previous study also demonstrated that CD38 played vital roles in adipogenesis and high fat induced oxidative stress (Wang et al, 2018a, b). But the role of CD38 in heart aging was unknown.…”
Section: Discussionmentioning
confidence: 78%
“…A number of evidences indicated that Sirtuin family had beneficial effects against age-associated damage and oxidative stress (Ho et al, 2009; Qiu et al, 2010; Someya et al, 2010; Tasselli et al, 2017). Our previous study showed that CD38 deficiency had protective roles in many cardiac diseases including ischemia/reperfusion injury, cardiac hypertrophy induced by Ang-II and lipid overload-induced heart injury (Guan et al, 2016; Guan et al, 2017; Wang et al, 2018a). However, whether CD38 affects heart aging and the mechanisms remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a CD38 inhibitor luteolinidin preserved NAD(P) + level, endothelial and myocardial function in an ex vivo heart I/R model (Boslett et al, 2017). The cardioprotective effect of CD38 deficiency have been shown to be SIRT1- (Guan et al, 2016) or SIRT3-dependent (Wang et al, 2018) in mouse models.…”
Section: Cd38 and Ca 2+ Signalingmentioning
confidence: 99%
“…In the next section, we will briefly describe genes associated with NDgD as AD, PD, and HD that were discovered by a GWAS approach and meta-analysis ( Qi et al, 2012b ; Moss et al, 2017 ; Chang et al, 2018 ; Jansen et al, 2019 ) and that had previously shown strong association with monogenic or polygenic obesity ( Tong, 2011 ; Hatziri et al, 2018 ; Wang et al, 2018a , b ; Liu et al, 2019 ). Some of the genes mentioned below are APOE and TREM2 associated with AD; CD38 variants with AD and PD; and SYT4 with PD ( Chang et al, 2018 ; Jansen et al, 2019 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%